2024
DOI: 10.1186/s12889-024-18338-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the medical decision-making patterns and influencing factors among the general Chinese public: a binary logistic regression analysis

Yuwen Lyu,
Qian Xu,
Junrong Liu

Abstract: Objective With the ongoing evolution of the healthcare system and shifts in cultural paradigms, there is a pressing need to delve into the medical decision-making behaviors of general Chinese public and understand their underlying motivations. This research seeks to elucidate the prevailing tendencies in these decision-making processes and to empirically validate the pivotal factors that shape their choices, offering valuable insights for healthcare policymakers and institutions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Medical decision-making is generally influenced by gender, educational levels, and certain occupational roles. 44 Previous evidence showed that education levels and workloads of WM were all significantly correlated with HCPs' medical decisions regarding TCM treatments. 38 Thus, a demographic questionnaire was administered to collect respondents' background information, including gender, position, education, professional title, work experience, level of hospitals, types of departments, and TCM workload.…”
Section: Measurementsmentioning
confidence: 97%
“…Medical decision-making is generally influenced by gender, educational levels, and certain occupational roles. 44 Previous evidence showed that education levels and workloads of WM were all significantly correlated with HCPs' medical decisions regarding TCM treatments. 38 Thus, a demographic questionnaire was administered to collect respondents' background information, including gender, position, education, professional title, work experience, level of hospitals, types of departments, and TCM workload.…”
Section: Measurementsmentioning
confidence: 97%